PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM PELATIHAN MENJAHIT DALAM TELAAH TEORI JIM IFE (STUDI KASUS PADA PANTI SOSIAL KARYA WANITA, NAIBONAT, KECAMATAN KUPANG TIMUR, KABUPATEN KUPANG) - Dina, Patrisia Kurnia; Syukur, Abdul; Makleat, Nirwaning (Education For All, 2023)
This study aims to determine the application of the four perspectives that have been put forward by Jim Ife in the theory of community empowerment at the Karya Wanita Social Institution, Naibonat. This research method uses a qualitative method with a case study approach. The subjects in this study were heads and staff of social institutions, assisted residents of social institutions, former assisted members, instructors, and parties from other institutions that work with social institutions. The research findings show that the four perspectives that have been put forward by Jim Ife, have been running in social institutions, as in the pluralist perspective, services have been provided such as sewing training and also social, physical, mental, and management guidance, then in the elitist perspective of the orphanage social services have collaborated with various parties such as social services, religious institutions, and also health agencies, then from a structuralist perspective the social institution has generalized all services for every inmate, and finally the post-structuralist perspective of the orphanage does not only focus on sewing training, but also provides other guidance.